Evolución sedimentaria y paleogeografía del Jurásico Superior (Kimmeridgiense superior-Titónico) en la Sierra de Arcos (Cordillera Ibérica) - Aurell, M.; Cepriá, J. J.; Bádenas, B. (Journal of Iberian Geology, 2002)
Facies analysis of the upper Kimmeridgian-Tithonian of the Sierra de Arcos (Iberian Chain) allowed the reconstruction of the sedimentary evolution during the deposition of two sequences, the so called J3.6 and J3.7 sequences defined by Aurell et al. (2000). Both sequences display a thin or even condensed transgressive systems tract, and a thick highstand and forced regressive systems tracts. Development of shallover facies in the distal part of the ramp was controlled by the so-called Montalbán-Ejulve High. Peloidal and oncolitic shoals were present during deposition of sequence J3.6, whereas peloidal shoals and coralgal patch reefs developed during the highstand of sequence J3.7. These set of shallow facies prograded over outer ramp facies (i.e., lime mudstone and marls). The influence of the sedimentary high is not obvious during deposition of the forced regressive systems tract of sequence J3.7, when the overall southeast progradation of the oolitic shoals and associated restricted environments took place.